2016
DOI: 10.1111/ipd.12232
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatasia: diagnosis and clinical signs – a dental surgeon perspective

Abstract: Summary Background Hypophosphatasia (HPP) is a rare inherited metabolic disease in which mutations in the ALPL gene (encoding tissue‐nonspecific alkaline phosphatase) result in varying degrees of enzyme deficiency. HPP manifests in a spectrum of symptoms, including early primary tooth loss (root intact) and alveolar bone mineralisation defects. Objective To provide an overview of HPP for dental professionals to help recognise and differentially diagnose patients for appropriate referral to a specialist team. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 51 publications
3
43
0
2
Order By: Relevance
“…Four patients were observed to have various degrees of enamel hypoplasia of the permanent teeth. Similar amelogenesis impairment of the permanent teeth in patients with HPP has also been described by Bloch‐Zupan A …”
Section: Discussionsupporting
confidence: 78%
“…Four patients were observed to have various degrees of enamel hypoplasia of the permanent teeth. Similar amelogenesis impairment of the permanent teeth in patients with HPP has also been described by Bloch‐Zupan A …”
Section: Discussionsupporting
confidence: 78%
“…Our patient was referred to a physician, and diagnosis was made based on low serum ALP levels and the radiographic dental findings. Numerous studies on dental characterization of HPP have been reported [5] [6], while few reports briefly described the dental management [7] [8]. We observed this patient from the stage of primary dentition to the mixed dentition period.…”
Section: Discussionmentioning
confidence: 72%
“…We believe that disorders of pyridoxine metabolism in epileptic families are the consequences of inborn hypophosphatasia caused by a low activity of TNSALP. Mutations in ALPL gene, which encodes TNSALP, are responsible for the reduction of enzymatic activity [71][72][73]. The clinical spectrum of congenital hypophosphatasia presents a wide variety of phenotypesfrom newborn, or infant convulsions controlled by pyridoxine [74][75][76][77][78][79] to their asymptomatic parents [80][81][82][83][84], whose ALP deficiency may be manifested, for example, by osteoarthropathy and/or odontohypophosphatasia.…”
Section: Discussionmentioning
confidence: 99%